2022
DOI: 10.1124/molpharm.121.000473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the TARP γ8-Selective Negative Allosteric Modulator JNJ-55511118 on AMPA Receptor Gating and Channel Conductance

Abstract: AMPA, α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid; AMPAR, AMPA receptor; CP-AMPARs, calcium permeable AMPARs; glu, glutamate; I peak , peak current; I ss , steady-state current; JNJ-118, JNJ-55511118; LBD, ligand binding domain; NSFA, non-stationary fluctuation analysis; P o, peak , peak open probability; RI, rectification index; TARP, transmembrane AMPAR regulatory protein; TM, transmembrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 65 publications
4
1
0
Order By: Relevance
“…6b and Supplementary Fig. 9a, b ), consistent with a recent study 39 . Similar to JNJ-118, LY-481 triggered a pronounced reduction of the equilibrium response, but modestly slowed GluA2_γ8 desensitization kinetics (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6b and Supplementary Fig. 9a, b ), consistent with a recent study 39 . Similar to JNJ-118, LY-481 triggered a pronounced reduction of the equilibrium response, but modestly slowed GluA2_γ8 desensitization kinetics (Fig.…”
Section: Resultssupporting
confidence: 92%
“…MD simulations reveal water molecules penetrating into the pocket from γ8 Ser128 on the extracellular edge down to γ8 Asn172 in the binding pocket (Supplementary Fig. 4a ), suggesting a potential route for ligand entry, with access via the lipid bilayer offering an additional route , , as also suggested in a recent study of JNJ-118 39 . Putative waters appear in the LY-481 cryoEM map around GluA2 Ser790, and in the NAM pocket at γ8 Ser128 (Supplementary Fig.…”
Section: Resultssupporting
confidence: 71%
“…This behaviour was not seen with JNJ-118, which acted as a NAM on GluA2 for all measures ( Fig. S9a and b ), consistent with a recent study 48 . Similar to JNJ-118, LY-481 triggered a pronounced reduction of the equilibrium response, but modestly slowed GluA2_γ8 desensitization kinetics ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…7a, b ). The promoting effect of JNJ55511118 on the desensitization of AMPARs was also consistent with a recent report, which identified that JNJ55511118 decreased peak currents and the time constant of desensitization of AMPARs 25 . Taken together, these results provide important insights into the rapid antidepressant effects of ketamine that is dependent on the potentiation of TARP-γ8-selective AMPAR-mediated synaptic transmission in the ventral hippocampus.…”
Section: Resultssupporting
confidence: 91%
“…A series of TARP-γ8 antagonists have been designed and synthesized, such as LY3130481 and JNJ55511118, which selectively antagonize AMPAR containing TARP-γ8, but not other TARP members 24 , 25 , 60 . Corresponding to this selective activity, LY3130481 was proved to prevent multiple epilepsy-related symptoms in mice without motor side effects 60 .…”
Section: Discussionmentioning
confidence: 99%